2018
DOI: 10.1177/2055668318761524
|View full text |Cite|
|
Sign up to set email alerts
|

Prompting arm activity after stroke: A clinical proof of concept study of wrist-worn accelerometers with a vibrating alert function

Abstract: Background Frequent practice of functional movements after stroke may optimise motor recovery; however, it is challenging for patients to remember to integrate an impaired limb into daily activities. We report the activity responses of stroke patients receiving a vibrating alert delivered by a tri-axial accelerometer wristband to prompt movement of the impaired arm if hourly activity levels fell. Methods Adults with upper limb impairment ≤28 days post-stroke wore the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 20 publications
2
27
1
Order By: Relevance
“…The median ARAT scores for both groups showed an improvement during the four-week study intervention phase with the intervention group continuing to improve up to the eight-week follow-up outcome. The amount of use of the impaired arm as measured by the MAL and the accelerometers also indicated an increase for both groups, which continued up to the week eight out- 15 (10)(11)(12)(13)(14)(15)(16)(17)(18) 19 (16)(17)(18)(19) 19 (17)(18)(19)(20) 12 (10)(11)(12)(13)(14)(15)(16) 17 (12)(13)(14)(15)(16)(17)(18)(19) 15 (15)(16)(17)(18) ARAT: Action Research Arm Test; IQR: interquartile range; NIHSS: National Institutes of Health Stroke Scale. come for the intervention group but not for the control group.…”
Section: Resultsmentioning
confidence: 95%
“…The median ARAT scores for both groups showed an improvement during the four-week study intervention phase with the intervention group continuing to improve up to the eight-week follow-up outcome. The amount of use of the impaired arm as measured by the MAL and the accelerometers also indicated an increase for both groups, which continued up to the week eight out- 15 (10)(11)(12)(13)(14)(15)(16)(17)(18) 19 (16)(17)(18)(19) 19 (17)(18)(19)(20) 12 (10)(11)(12)(13)(14)(15)(16) 17 (12)(13)(14)(15)(16)(17)(18)(19) 15 (15)(16)(17)(18) ARAT: Action Research Arm Test; IQR: interquartile range; NIHSS: National Institutes of Health Stroke Scale. come for the intervention group but not for the control group.…”
Section: Resultsmentioning
confidence: 95%
“…The greater odds of moving the affected UL in the minute following a planned nudge resulted in a 32.2% increase in the average amount of movement. Another small-scale proof-of-concept study involving people with stroke (n=7) [ 30 ] indicated an increase of 19.7% in the average amount of affected UL movement in the hour following a haptic nudge reminder to undertake exercises. In that study, participants were instructed to perform up to 80 repetitions of task-specific training in response to a haptic nudge, but only received a median of 4 nudges across the rehabilitation day.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary indications suggest that wearable devices may increase the amount and intensity of physical activity undertaken during rehabilitation [ 26 - 28 ] and potentially contribute to improved functional outcomes [ 29 ]. However, the effect of wearable devices on UL rehabilitation and outcomes has been less well studied [ 30 , 31 ], with much of the research to date focusing on the accuracy and validity of accelerometry measurement of real-world UL movement [ 32 - 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, none of these products are tailored to people with movement impairments and thus have limited usefulness for them. Recently, few studies have been initiated to evaluate the effectiveness of providing feedback on arm activity [22,23] .…”
Section: Upcoming Technologies: Wearable Sensing For Monitoring Arm Amentioning
confidence: 99%